THE USE OF MATHEMATICS SOFTWARE DURING STUDY OF THE ACADEMIC DISCIPLINE OF PHYSICS - Soloshich, Іrina; Kobilskaya , Olena; Lyashenko, Viktor (Physical and Mathematical Education, 2022)
Formulation of the problem. Higher education students must have an understanding of computer models, be fluent in modern software products, including mathematics software, and be able to use them in solving physical problems. The use of mathematics software Mathcad helps to gain skills in analyzing and finding optimal solutions to problems, that arise not only in the study of "Physics", but also in solving professional problems, increases students' interest in studying physics, improves academic performance .Materials and methods. In the course of the research, the following methods were used: theoretical (analysis of scientific and methodological literature to identify the state of development of the problem of using the capabilities of computer mathematics systems in the study of the academic discipline «Physics»); empirical (observation, analysis and systematization). To solve the problems of the  subfield of physics «Kinematics» it is proposed to use the mathematics software Mathcad. It is shown how, using Mathcad tools, one can integrate expressions, build graphs of a function, solve a system of equations (Given-Find block), search for the maximum value (Given-Maximize block).Results. The paper investigates the methodological aspects of using the mathematics software Mathсad for solving practical problems in the academic discipline «Physics». Several problems of the subfield of physics «Kinematics» are considered, including the problems in which the extreme values of the sought quantities are determined (maximum height, maximum angle of inclination). To solve the problems, it was proposed to use the mathematics software Mathcad. It is shown that Mathcad makes it possible to effectively implement such important stages of solving the problem of finding an extremum as: plotting, differentiating, searching for an extremum using special functions in Mathcad. It is noted that the use of the mathematics software Mathcad contributes to the acquisition of the skills of analysis and the search for optimal solutions not only during the study of the academic discipline «Physics», but also during the solution of professional problems, increases the interest of students in the study of physics, improves the results of educational achievements. The use of mathematics software in the educational process during the study of the discipline «Physics» due to the powerful graphics, visual programming tools has a positive effect on the mastery of students the skills of practical use of professional knowledge based on the laws of physics.Conclusions. In modern realities in the introduction of information technology in the educational process, one of the most important ways to improve the study of «Physics is to use mathematics software for numerical calculations in solving problems, processing experimental data and studying physical phenomena. The introduction of the mathematical software Mathcad during the study of the academic discipline «Physics» has shown its effectiveness, because a wide range of capabilities of this software package allows you to effectively solve problems of varying degrees of complexity, contributes to a deeper understanding of physical laws and phenomena both during classroom lessons and during independent learning.
Keywords: mathematical software; academic discipline «Physics»; practical classes; problems of kinematics; extreme values